The Response of the Aerosol Distribution to Monsoon Intensity Over the Summer Monsoon Transition Zone - Bai, Bing; Zhang, Qiang; Shao, Wei; Wang, Ying; Tan, Dan (Frontiers in Earth Science, 2020)
The study area was the East Asian summer monsoon (EASM) transition zone.[1College of Atmospheric Science, Lanzhou University, Lanzhou 730020, China 2Key Laboratory of Arid Climatic Change and Reducing Disaster of Gansu Province/Key Open Laboratory of Arid Climatic Change and Reducing Disaster of CMA, Institute of Arid Meteorology, China Meteorological Administration, Lanzhou 730020, China 3Gansu Meteorological information and Technic Support and Equipment Center, Lanzhou 730020, China 4Lanzhou Central Meteorological Observatory, Lanzhou 730020, China ] Using daily data for the 2008–2016 period from national stations and the European Centre for Medium-Range Weather Forecasts (ECMWF), combined with Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) and Moderate Resolution Imaging Spectroradiometer (MODIS) satellite data, the influence of EASM circulation on aerosol optical depth (AOD) in the transition zone and the response of different kinds of aerosols in the transition zone to abundant and deficient monsoon years was analyzed. It was found that the AOD was 0.15 in abundant years, while it was 0.09 in deficient years. The abundant year’s AOD was 40% larger than deficient years. In deficient years, with less precipitation, the influence of precipitation on the AOD was more significant. The dust was mainly distributed at 2–6 km in the western part of the transition zone, while the polluted aerosols were distributed at 0–4 km in the central and eastern region. In abundant monsoon years, the frequency of occurrence of dust aerosols was significantly lower than in deficient monsoon years, with dust particles accounting for about 19.6% of the total aerosol, while the frequency of occurrence of polluted aerosols displayed the opposite trend, accounting for about 46.5% of the total aerosol and being more frequent in abundant rather than deficient monsoon years.